A randomized trial of collaborative support for opioid taper after trauma hospitalization - Mark D. Sullivan; Laura Katers; Jin Wang; Sam Arbabi; David Tauben; Laura-Mae Baldwin (BMC, 2024)
Abstract The COTAT (Collaborative Opioid Taper After Trauma) Study was a randomized trial of an opioid taper support program using a physician assistant (PA) to provide pain and opioid treatment guidance to primary care providers assuming care for adult patients with moderate to severe trauma discharged from a Level I trauma center on opioid therapy. Patients were recruited, assessed, and randomized individually by a surgery research recruitment team one to two days prior to discharge to home. Participants randomized to the opioid taper support program were contacted by phone within a few days of discharge by the PA interventionist to confirm enrollment and their primary care provider (PCP). The intervention consisted of PA support as needed to the PCP concerning pain and opioid care at weeks 1, 2, 4, 8, 12, 16, and 20 after discharge or until the PCP office indicated they no longer needed support or the patient had tapered off opioids. The PA was supervised by a pain physician-psychiatrist, a family physician, and a trauma surgeon. Patients randomized to usual care received standard hospital discharge instructions and written information on managing opioid medications after discharge. Trial results were analyzed using repeated measures analysis. 37 participants were randomized to the intervention and 36 were randomized to usual care. The primary outcomes of the trial were pain, enjoyment, general activity (PEG score) and mean daily opioid dose at 3 and 6 months after hospital discharge. Treatment was unblinded but assessment was blinded. No significant differences in PEG or opioid outcomes were noted at either time point. Physical function at 3 and 6 months and pain interference at 6 months were significantly better in the usual care group. No significant harms of the intervention were noted. COVID-19 (corona virus 2019) limited recruitment of high-risk opioid tolerant subjects, and limited contact between the PA interventionist and the participants and the PCPs. Our opioid taper support program failed to improve opioid and pain outcomes, since both control and intervention groups tapered opioids and improved PEG scores after discharge. Future trials of post-trauma opioid taper support with populations at higher risk of persistent opioid use are needed. This trial is registered at clinicaltrials.gov under NCT04275258 19/02/2020. This trial was funded by a grant from the Centers for Disease Control and Prevention to the University of Washington Harborview Injury Prevention & Research Center (R49 CE003087, PI: Monica S. Vavilala, MD). The funder had no role in the analysis or interpretation of the data.